2003
DOI: 10.1079/wps20030013
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of gut associated immune competence in the chick

Abstract: To accommodate the rapid transition to external nutrients, the chick's gastrointestinal tract undergoes dramatic changes within the first few days of life. These include a rapid increase in mass, villi number and length, enterocyte number, crypt depth and proliferating cells. Concomitant with the development of digestive structures and functions a rapid development of the gut associated lymphoid tissue (GALT) occurs. This lymphoid system works within and in concert with digestive tract parenchyma, however, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 53 publications
1
39
1
2
Order By: Relevance
“…Previous studies demonstrated that early feed intake (immediately after hatch) enhances the functional development of the intestines in chicks that results in increased digestibility and thereby growth (Noy et al, 2001;Friedman et al, 2003). This explains the higher BW of optimized chicks in the first 3 weeks posthatch in this study.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies demonstrated that early feed intake (immediately after hatch) enhances the functional development of the intestines in chicks that results in increased digestibility and thereby growth (Noy et al, 2001;Friedman et al, 2003). This explains the higher BW of optimized chicks in the first 3 weeks posthatch in this study.…”
Section: Discussionsupporting
confidence: 69%
“…The functional development of the intestines as a digestive organ seems to be closely related to its development as a major lymphoid organ (Thompson et al, 1996). Previous studies showed that early feed intake has a positive effect on the development and maturation of the gut associated lymphoid tissue (GALT), which includes the cecal tonsils, bursa of Fabricius, Peyer's pathes and other lymphoid nodules, and provides both local and systemic protection in young chicks (Dibner et al, 1998;Friedman et al, 2003;Kajiwara et al, 2003). Delayed access to feed has shown to decrease bursa weight (Dibner et al, 1998) and to delay the development of T and B lymphocytes in the hindgut in the first 2 weeks of life (Bar-Shira et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the authors' view, such retrograde motility of the middle intestine improves reabsorption of urine and caecal contents, and provides better absorption of cellulose degradation products and crude protein (82)(83)(84). Such reverse peristalsis between the middle part of jejunum, duodenum, and even gizzard, was observed in both newly hatched chicks and in adult chickens (85). So, it is possible that external material enters immunoactive caecal appendices, and, moreover, that antibodies may uplift from the bursal sac into the small intestine.…”
Section: Gut Defenses In Birds (Explanation -See Below)mentioning
confidence: 89%
“…The colon of birds has no lymphoid follicles, but they occur in its terminal part opening into the cloacal bursa -a lymphoid organ located in proctodeal part of the cloaca and involved in primary and secondary immune responses. Mucosa and submucosa of the bursal duct contain many lymphoid follicles (85). There are single lymphoid nodes in procdeum (hindgut) and urodeum (part of cloaca near urethral orifices) (54).…”
Section: Intraepithelial Lymphocytes Of Chickens Are Represented By Amentioning
confidence: 99%
“…Furthermore, even if a wide range of ingredients were available, the preparation of adequate diets is difficult to achieve in commercial systems because of the limited storage available to feed compounders. Birds fed conventional diets that provide methionine at suboptimal levels have been shown to be predisposed to health-, welfare-and productionrelated problems (Friedman et al, 2003;Kidd, 2004;Klasing, 2006). Furthermore, birds cannot necessarily compensate for inadequate amino acid levels by increased food intake (Whitehead, 2002).…”
Section: Introductionmentioning
confidence: 99%